Breaking Even or Breaking Through : Reaching Financial Sustainability while Providing High Quality Standards in Higher Education in the Middle East and North Africa - Jaramillo, Adriana; Melonio, Thomas (World Bank, Washington, DC, 2016)
Higher education (HE) systems worldwide are faced with three main challenges: providing young people with the skills required by the job market; improving access to high quality services; and seeking out new sources of financing to cope with the growing student demand. This document will provide evidence on the need to seek sustainable financing strategies for countries in Middle East and North Africa (MENA), whether they are high income economies, such as the oil producing countries, or low to middle income economies. Chapter one presents an overall description of HE graduates and the many challenges they face in their transition into the workforce. The different elements that affect this transition are discussed and special attention is given to the mismatches between labor supply and demand. Chapter two analyses the current levels of spending on HE, projects the future financing gaps taking into account the need to continue expanding access and improving quality and relevance, and provides a framework for funding approaches linked to meeting access, equity, and quality goals. Chapter three outlines ways of using current funds in more effective ways, emphasizing the need to align financing allocations with policy goals. Innovative funding allocations that link funding to performance and demand- as well as supply-side mechanisms are discussed. Chapter four discusses different ways to diversify sources of funding and presents alternative methods of cost-sharing. The chapter emphasizes the equity measures needed for cost-sharing mechanisms, such as student fees, and provides an overview of student loan programs used in MENA and elsewhere. Chapter five discusses the role of private provision of HE, and how this can be an alternative to increase access and quality, provided the necessary regulatory and quality controls are in place. Chapter six describes an alternative source of funding not yet common in MENA, namely the use of philanthropic resources to build endowments to support HE.